Transformasi Kesehatan melalui Perbaikan Sanitasi: Kiprah dr. Budi Laksono sebagai Relawan Kesehatan, 1991-2019 - Hutapea, Ckrystin Natalia; Utama, Mahendra Pudji (Department of History, Faculty of Humanities, Diponegoro University, 2023)
This article exposes dr. Budi Laksono's career journey as a volunteer aimed at improving the health of Indonesian people, transitioning them from less healthy to healthier lifestyles. To uncover dr. Budi Laksono's role in improving societal health, this study adopts a historical method with a biographical approach. This approach aims to unveil the actions taken by dr. Budi Laksono that have contributed to this endeavor. It is known that dr. Budi Laksono is a doctor who deeply concerned with Indonesian public health, encountered numerous patients suffering from gastrointestinal diseases during his tenure as a general practitioner. These diseases were attributed to unsanitary living conditions in the area. Driven by a desire to address this issue, he focused on enhancing the health of the villagers, whose known for their suboptimal sanitation. His experiences in health improvement initiatives in the region inspired him to advocate for the importance of sanitation nationwide. He initiated various movements, including the